Extreme C‐terminal element of SprA serine integrase is a potential component of the "molecular toggle switch" which controls the recombination and its directionality. Issue 6 (13th December 2020) - Abe, Kimihiro; Takahashi, Takumi; Sato, Tsutomu
Abstract: In Bacillus subtilis, a sporulation‐related gene, spsM, is disrupted by SPβ prophage, but reconstituted during sporulation through SPβ excision. The spsM reconstitution is catalyzed by a site‐specific DNA recombinase, SprA, and its cognate recombination directionality factor, SprB. SprB interacts with SprA, directing the SprA‐mediated recombination reaction from integration to excision; however, the details of the directionality control remains unclear. Here, we demonstrate the importance of the extreme C‐terminal region (ECT) of SprA in the DNA recombination and directionality control. We created a series of SprA C‐terminal deletants and examined their DNA‐binding and recombination activities. Deletions in the ECT caused a loss of integration and excision activity, the magnitudes of which positively correlated with the deletion size. Gel shift study revealed that the loss of the integration activity was attributable to the failure of synaptic complex formation. The excision deficiency was caused by defective interaction with SprB. Moreover, alanine scanning analysis revealed that Phe532 is essential to interact with SprB. SprAF532A, therefore, showed almost no excision activity, while retaining the integration activity. Collectively, these results suggest that the ECT plays the crucial roles in the interaction of SprA with SprB and possibly in the directional control of the recombination. Abstract : The extreme C‐terminal region (ECT) of a site‐specific DNA recombinase, SprA, from Bacillus subtilis temperate phage SPβ is required for formation of synaptic complex (SprA tetramer containing DNA targets) during recombination. Moreover, Phe532 residue is essential to interact with its cognate recombination directionality factor, SprB, which is required for phage excision.